The Correlation Between Nurse Performance Evaluation Indicators and Nurse Work Productivity at Wijaya Kusuma Hospital - Ernawati; Dodik Hartono; R. Endro Sulistyono (KHD Production, 2024)
Performance appraisal is a process within an organization that aims to evaluate employee performance. Performance appraisal is used to assess how much productivity is produced by employees. One of the main challenges many organizations face today is increasing employee productivity. This research aims to determine the relationship correlation performance assessment indicators and the work productivity of nurses at Wijaya Kusuma Hospital, Lumajang. The research design used analytical observational with a cross-sectional approach. The population included all nurses at Wijaya Kusuma hospital Lumajang totaling 79 nurses. The instruments used an employee performance assessment questionnaire within the Ministry of Health and IWPQ. Next, it was analyzed using the Spearman's rho test.This research has been submitted and passed ethics at KEPK Unhasa. The results of this research showed that 31 respondents (39.2%) performed in the very good category, 30. The number of respondents with an assessment of work productivity evaluation of work productivity in the Medium category was 48 (60.8%). The nurse performance assessment indicator significantly correlated with work productivity, as indicated by a correlation coefficient of 0.905 with a significance level of 0.001 (P0.05). Performance appraisal not only functions as an evaluation tool but also as an instrument for sustainable performance development. Hospitals should continue to improve their performance assessment systems, which are objective and support the development of nurse competency. With proper assessment, it is hoped that there will be a sustainable increase in work productivity, which will ultimately positively impact the quality of health services.